Enterprise risk management and information technology security in the financial sector. (8th February 2022) - Owusu Kwateng, Kwame; Amanor, Christopher; Tetteh, Francis Kamewor
Abstract : Purpose: This study aims to empirically investigate the relationship between enterprise risk management (ERM) and information technology (IT) security within the financial sector. Design/methodology/approach: Risk officers of financial institutions licensed by the Central Bank of Ghana constituted the sample frame. A structured questionnaire was used to elicit data from the respondents. The structural equation modeling method was employed to analyze the hypothesized model. Findings: The results revealed that ERM has a strong positive substantial effect on IT security within financial institutions. However, organizational culture failed to moderate the relationship between ERM and IT security. Practical implications: A well-managed risk helps to eliminate ineffective, archaic and redundant technology as the originator of rising perils and organizational concerns in today's corporate financial institutions since ERM established a substantially strong positive correlation among the variables. Originality/value: ERM studies in the African context are rare. This paper adds to contemporary literature by providing a new perspective toward the understanding of the relationship between ERM and IT security, especially in the financial industry.